Kualitas Metode Penelitian Kualitatif Program Strata 1 dalam Pengarusutamaan Gender : Telaah Awal - Heri Junaidi (Pusat Studi Gender dan Anak Universitas Islam Negeri Raden fatah palembang, 2019)
This journal from the study entitled Improving the Quality of Qualitative Research Methods and Study of Figures in Gender Mainstreaming Material for Strata 1 Students. The initial study of this study departs from research results that are refuted from the results of research on how to find experts in research that found two main findings, namely: First, issues that develop among students discussing lecture questions that are easy to understand but difficult to implement; Secondly, the failure of students to build motivation is closely related to systematic in the research effort. In many cases this starts from (1) the difficulty of finding the first word in each time it will write, concocting word choices and finding relationships between paragraphs; (2) developing patterns of making intuitive standard papers without reference and most extreme by learning through copy paste of papers on the internet. Therefore the contribution of the results of the questionnaire answers became the main data for the development of this study